2016
DOI: 10.1142/s1363919616500079
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Knowledge-Integration Practices in Service Innovation Projects

Abstract: Services comprise an increasingly bigger proportion of contemporary economies, making service innovation more relevant than ever. However, the practices and processes related to the utilisation of knowledge for service development are not very well understood in this context. To narrow this gap, this study focuses on how Knowledge-Intensive Business Service (KIBS) firms utilise knowledge-integration practices in different phases of the service-innovation projects they carry out for their customers. A multiple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For knowledge integration into the value creation process, Grant (1996a) identified four mechanisms that several scholars have elaborated (Heugens et al 2004;Spanos and Prastacos 2004;Canonico et al 2012;Hurnonen et al 2016): (1) rules and directives, (2) sequencing, (3) routines, and (4) group problem solving and decision making. They aim to integrate the knowledge efficiently, defined as effectively integrating, while minimizing the transfer, which is dependent on process characteristics, division of tasks between individuals, and organizational design (Grant 1996a).…”
Section: The Source Of Knowledge-based Competitive Advantagementioning
confidence: 99%
See 2 more Smart Citations
“…For knowledge integration into the value creation process, Grant (1996a) identified four mechanisms that several scholars have elaborated (Heugens et al 2004;Spanos and Prastacos 2004;Canonico et al 2012;Hurnonen et al 2016): (1) rules and directives, (2) sequencing, (3) routines, and (4) group problem solving and decision making. They aim to integrate the knowledge efficiently, defined as effectively integrating, while minimizing the transfer, which is dependent on process characteristics, division of tasks between individuals, and organizational design (Grant 1996a).…”
Section: The Source Of Knowledge-based Competitive Advantagementioning
confidence: 99%
“…They aim to integrate the knowledge efficiently, defined as effectively integrating, while minimizing the transfer, which is dependent on process characteristics, division of tasks between individuals, and organizational design (Grant 1996a). These mechanisms, especially the first three, can be rather impersonal, communication minimizing, and knowledge transfer economizing (''automating'' or ''programming'') (Ven et al 1976;Grant 1996a;Alavi and Leidner 2001;Spanos and Prastacos 2004;Hurnonen et al 2016). In contrast, lateral relationships that are personal, less straightforward, and interaction dependent can be deployed as in the fourth mechanism (Galbraith 1973;Grant 1996a;Canonico et al 2012).…”
Section: The Source Of Knowledge-based Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Their results demonstrate that a learning competency drives development competency, which, in turn, drives NSD performance. Hurnonen et al (2016) identified two types of serviceinnovation projects that capture the seminal knowledge-based debate about whether the role of the organization is to maximize knowledge sharing and creation or to minimize both and concentrate on the efficient utilization and integration of highly skilled expertise. Kuester et al (2013) study innovation activities and the importance of service innovations' success factors within various service industries.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Moreover, they asserted that any knowledge intensive business service is key to enhancing innovative capability (Muller & Zenker, 2001). Besides, Hurnonen et al (2016) concluded that service innovation development is supported by choosing relevant knowledge integration practices. Nawab et al (2015) concluded that knowledge management processes are contributing in the enhancement of innovation in banking industry.…”
Section: Knowledge Management Processes and Service Innovationmentioning
confidence: 99%